1 - Economic Security in an Agrarian Community - Mtika, Mike Njalayawo (Africa Development, 2021)
Free-market capitalism creates great wealth but is disempowering and produces widespread poverty, inequality, and human despair; it generates economic insecurity for the masses. A main reason for this is that free market capitalism operates from an exogenous perspective; it is guided by marginal utility and marginal productivity. What we need is capitalism that integrates endogenous and exogenous processes. This approach focuses on building creativity, innovativeness, and ingenuity in how people use resources to make a living. In this paper, I draw on what is happening in the Zowe community development program in northern Malawi where we have started what I have termed community entrepreneurship to propose a model of this approach to wealth generation and accumulation. The community entrepreneurship process I discuss in the paper is both exogenous and endogenous in that it focuses on (a) building entrepreneurial knowledge, skills, and capacity in communities and (b) propagating innovative, creative, and responsible behavior in the way people make a living. I conclude that following both endogenous and exogenous economic principles is one way for agrarian societies to attain economic security